Timor-Leste: The Adventurous Tribulations of Local Governance after Independence - Feijó, Rui Graça (2015)
Xanana Gusmão recently mentioned that a “Second Maubere Miracle” is underway, implying that a major political reform will soon shake the roots of Timor-Leste’s public administration. Decentralization, defined in a very broad sense, has been a constitutional mandate since independence, but successive governments have failed to engage this reform despite paying lip service to its necessity. This essay reviews the options before the policy makers – both in theoretical terms (distinguishing between the various definitions of decentralization) and in the pragmatic forms that have been contemplated so far – and discusses their implications for the process of rooting a modern democracy in the country both at the intermediate, district level and at the grassroots, suku (village) level. For this purpose, the essay brings together the author’s own field research and the rich literature that has emerged in the recent past, including contributions by Timorese colleagues.